2014
DOI: 10.1177/1534735414542484
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Measured Using Global Positioning System Tracking in Non–Small Cell Lung Cancer

Abstract: Global positioning system tracking appears to be a feasible methodology for adult cancer patients and holds promise for use in future studies investigating PA and or lifestyle behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…5 In people with lung cancer, data on PA and SB are limited. Studies have reported low levels of PA in people with non-small cell lung cancer (NSCLC), 6,7 however, these studies have not explored SB or the way in which time is accumulated in SB or PA performed at any intensity. Obtaining data on patterns of SB and PA in this population and comparing these data with those collected in healthy controls will allow health professionals to provide novel targets for rehabilitation interventions.…”
mentioning
confidence: 99%
“…5 In people with lung cancer, data on PA and SB are limited. Studies have reported low levels of PA in people with non-small cell lung cancer (NSCLC), 6,7 however, these studies have not explored SB or the way in which time is accumulated in SB or PA performed at any intensity. Obtaining data on patterns of SB and PA in this population and comparing these data with those collected in healthy controls will allow health professionals to provide novel targets for rehabilitation interventions.…”
mentioning
confidence: 99%
“…The KinetaMap accelerometer demonstrated weaker evidence of construct validity. 26 Responsiveness of the ActivPaL, 24 Sensewear 27 and Lifecoder 28 devices was reported using step count changes over time. No other reporting of measurement properties for accelerometers was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Distance‐based PA interventions in breast, colon and rectal cancer survivors ranging from 12 to 16 weeks long report increases in PA ranging from 12 to 71 min/week (Ligibel et al., ; Pinto et al., ; Vallance et al, ). Research has indicated that lung cancer survivors report very low levels of MVPA (Coups et al., ; Granger, Denehy, et al., ). The current results suggest that participants were accumulating over two additional sessions of MVPA per week following our PA intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The goal was to progress towards achieving 150 min of moderate PA per week, which is the current aerobic exercise recommendations for cancer survivors (Schmitz et al., ). The intervention focused on increasing walking, which constitutes the majority of daily PA and is the most common, and preferred, form of PA among lung cancer survivors (Granger, Denehy, et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation